113 Clinical Presentation Phenotypes of Patients Operated for Lumbar Spondylolisthesis: An Analysis of the Quality Outcomes Database. (1st March 2022) - Chan, Andrew K.; Wozny, Thomas A.; Bisson, Erica F.; Pennicooke, Brenton H.; Bydon, Mohamad; Glassman, Steven D.; Foley, Kevin T.; Shaffrey, Christopher I.; Potts, Eric A.; Shaffrey, Mark E.; Coric, Domagoj; Knightly, John J.; et al.
Abstract : INTRODUCTION: Trials of lumbar spondylolisthesis are difficult to compare due to heterogeneity in the populations studied. METHODS: This is a study of the prospective Quality Outcomes Database Spondylolisthesis Registry, including patients who underwent single-segment surgery for grade 1 degenerative lumbar spondylolisthesis. Twenty-four-month patient-reported outcomes (PROs) were compared. A k-means clustering analysis—an unsupervised machine learning algorithm—was used to identify clinical presentation phenotypes. RESULTS: Overall, 608 patients were identified, of which 507 (83.4%) had 24-month follow up. Clustering revealed 2 distinct cohorts. Cluster 1 (high-disease-burden) was younger, had higher BMI and ASA grades, and globally worse baseline PROs. Cluster 2 (intermediate-disease-burden) was older, had lower BMI and ASA grades, and intermediate baseline PROs. Baseline radiographic parameters were similar (p > 0.05). In multivariable adjusted analyses, mean 24-month ODI, NRS-back pain, NRS-leg pain, and EQ-5D were markedly worse for the high-disease-burden cluster (adjusted p < 0.001). However, the high-disease-burden cluster demonstrated greater 24-month improvements for ODI, NRS-back pain, and EQ-5D (adjusted-p < 0.05) and a higher proportion reaching ODI minimal clinically important difference (MCID) (adjusted-p = 0.001). High-disease-burden cluster had lower satisfaction (adjusted-p = 0.02). CONCLUSION: We define two distinct phenotypes—those with high- versus intermediate-disease-burden—operated for lumbar spondylolisthesis. Those with high-disease-burden were less satisfied, had a lower quality of life, and more disability, more back pain, and more leg pain than those with intermediate-disease-burden, but had greater magnitudes of improvement in disability, back pain, quality of life and more often reached ODI MCID.